Pengembangan Formula Nanoemulsi Air dalam Minyak Biji Anggur (Vitis vinifera L.) sebagai Basis Lipstik - Siti Zahliyatul Munawiroh; Agenilia Permatasari; Lutfi Chabib (MPI (Media Pharmaceutica Indonesiana), 2019)
The objective of this research is to develop water in grape seed oil nanoemulsions which prepared by low energy method to be used in lipstick base formulation. Water in grape seed oil nanoemulsions were prepared by low energy methods which was employed a Phase Inversion Composition (PIC) technique in elevated temperature at 80°C using mixed-surfactants (tween 20/span 80). In ternary phase diagram (oil:water:mixed-surfactants), the largest area of nanoemulsions was occurred in equal ratio tween 20:span 80 (1:1). The maximum water content of water in grape seed oil nanoemulsions was reached at 20% water with 60% mixed-surfactants (1:1). An unimodal size distribution of water in grape seed oil nanoemulsions with varied water content at 6, 10, and 14% were found with droplet size at 29.33 ± 5.30, 30.23 ± 7.33, and 29.83 ± 11.47 nm. Water content of water in grape seed oil nanoemulsions insignificantly affected to melting profile and hardness properties of lipstick. Water in grape seed oil nanoemulsions which was prepared by low energy can be developed as lipstick base formulation.